EKSPLORASI INFORMASI KEANEKARAGAMAN JENIS, POTENSI DAN PEMANFAATAN TUMBUHAN BAHAN PESTISIDA ALAMI DIPROPINSIJAWA BARAT DAN BANTEN - Aseng Ramlan; Iin Supartinah Noer (Research Center for Biology-Indonesian Institute of Sciences, 2002)
Pests, diseases and weeds are considered as organisms that limiting the agricultural productivity. Losses of agricultural productivity originated from the attack of these organisms may be up to 40% to 60%; sometimes in several cases failure of harvests occurred. So far, chemical (synthetic) pesticides are used to control the attack of these organisms. Meanwhile, the use of synthetic pesticides in fact, creates many negative effects on both biotic and abiotic environments, such as pollution against terrestrial and aquatic environments, even killing the vertebrates and husbandry animals, predatory insects, and some economic insects (insect species that benefit to the life of man). Due to the losses created by utilization of synthetic pesticides, therefore a number of scientists and farmers initiated to turn their attention to use the natural pesticides (directly originated from plants) under the light of back to nature principle, although this step is seems to be less effective.Some natural pesticides practiced by West Javan farmers are likely almost disappeared and difficult to be found in the field. It is important to mention some species here such as cujete/kalabas (Cresentia cujete), bratawali (linospora tuberculata), bitter yam/gadung (Dioscorea hispida), sambiloto Andrographis paniculata), sarikaya Annona squamosa) and so many more. Some weed species are known used by farmers as natural pesticide like saliara Lantana camara), ki pahit (Tithonia diversifolia), alang-alang (Imperata cylindrical) and badotan Ageratum conyzoides). This research is aimed to inventory plant species used by farmers as natural pesticides as to reduce the reliance on synthetic pesticides. Methods of approach to the problem are by library studies (journals, proceedings of seminars, notes etc), field survey and interview to farmers of several districts (Kabupatens) in West Java and Banten Provinces i.e. Sumedang, Majalengka, Sukabumi, Garut, Pandegelang and Serang. Result shows that there are still 130 plant species used as natural pesticides, and 42 natural (plant based raw materials) pesticide formulations used by farmers.",